Data on the characterization of seaweed, wheat bran, and other food processing byproducts as feasible biosorbents - Robalds, Artis; Bikovens, Oskars; Dēliņa, Aija; Ponomarev, Nikolai P.; Purmalis, Oskars; Tomsone, Laura Elina; Vanags, Edgars (Elsevier Inc., 2024)
Traditionally, biosorbents have been used to remove contaminants from polluted water, such as wastewater, landfill leachate, rainwater or drinking water. However, two alternative uses of biosorbents have been proposed relatively recently: the removal of heavy metals from fruit juices by biosorption and the use of saturated biosorbents as animal feed. Because these biosorbents are in contact with food or are used as animal feed, the concentration of contaminants in biosorbents must be known. In addition, the characterization of biosorbents is crucial because biosorbent properties affect both adsorption efficiency and the performance of full-scale biosorbent systems. This article presents data from Fourier transform infrared spectroscopy (FTIR) analysis, and the concentration of toxic metals (determined by ICP-MS) as well as pesticide residues was determined in ten biomass samples, namely, pea skins, straw, seaweed Fucus vesiculosus, wheat bran, rye bran, raspberry seeds, peat, buckwheat husks, highbush blueberry pulp, and blackcurrant pulp. Selected biomass samples were also characterized by scanning electron microscopy (SEM), nitrogen physisorption analysis, and pyrolysis-gas chromatography-mass spectrometry (Py-GC/ MS/FID) analysis. © 2024 The Authors --//-- This is an open access article Artis Robalds, Oskars Bikovens, Aija Dēliņa, Nikolai P. Ponomarev, Oskars Purmalis, Laura Elīna Tomsone, Edgars Vanags, Data on the characterization of seaweed, wheat bran, and other food processing byproducts as feasible biosorbents, Data in Brief, Volume 53, 2024, 110214, ISSN 2352-3409, https://doi.org/10.1016/j.dib.2024.110214 published under the CC BY-NC-ND licence.
Keywords: Research Subject Categories::NATURAL SCIENCES; Analytical pyrolysis; Biomass; Biosorption; Fourier transform infrared spectroscopy; Pesticide residues; Toxic metals